(untitled) (Jurnal Pendidikan dan Bahasa Sastra Harapanan, 2024)
Studies on the influence of Islamic law in Indonesia can be one basis for muslims to define the future strategy of the Indonesian nation closer or familiarizing with Islamic law that has the effect of legal politic in Indonesia. At least it show sthat the influence of the process of Islamization of a society is nothing that can be completed immediately, but the center of attention is focused on the legal position of Islam can influence on legal politic in indonesia whic his polarized in the establishment of the legal system. Political policy in the law not only in legal proceedings that will be and are being enforced but includes also the law that have occurred, have practical purposes to allow positive legislation can be better formulated so as to provide guidance not only on legislation but also to the Courts as an organizer or as an implementing decision. -is has been experienced by the people of Indonesia since the era Dutch colonial that changed significantly when the Indonesian republic independent on 17th of August 1945, because they have to adjust in accordance with applicable law and the constitutional foundation the state ideology of Pancasila and the Constitution of 1945 or a law that is built upon the activity and creativity based upon ideals that is sourced on the cultural values of the nation which has long since evolved to the present